Optical properties of irradiated imidazolium based room temperature ionic liquids: new microscopic insights into the radiation induced mutations1. Issue 16 (28th April 2015) - Guleria, Apurav; Singh, Ajay K; Adhikari, Soumyakanti
<x xml:space="preserve">Abstract</x> The optical properties of electron beam irradiated RTILs revealed significant changes in the molecular rearrangements and realignment of bonding interactions. This study could be useful for comprehensively understanding the radiation driven effects in the ILs.